“It’s nothing personal”: understanding barriers to relational harm reduction practices during inpatient hospitalization - Kelsey Leon; Rachel Weger; Nate Weinstock; Raagini Jawa; J. Deanna Wilson (Harm Reduction Journal)
Abstract Background People who use drugs (PWUD) have a higher incidence of infectious complications that require medical interventions only available in hospital settings. Hospitalizations for PWUD are also more likely to result in patient directed discharge (PDD) before completing medical treatment. Stigma directed at PWUD pressurizes and shapes clinical encounters, leading to poor communication between patient and provider. We explore how the relational philosophy of harm reduction – the premise that building relationships rooted in compassion and respect, as opposed to a transactional encounter – can redress the harms and communication barriers between PWUD and healthcare providers in the hospital setting. Methods We recruited sixteen patients (achieving thematic saturation) with substance use disorder during their hospital stay at a large academic medical center with an urban, suburban, and rural referral base. Interviews were semi-structured, and focused on assessing patient knowledge and experiences of accessing harm reduction services and medical care. Interviews were transcribed verbatim and analyzed using content and thematic analysis. Findings When discussing patient experiences accessing medical care, three key themes emerged from our interviews about their hospital experiences: 1) providers disregard for social contexts of PWUD, 2) providers withholding care because of patient’s substance use, 3) patients viewed in negative or pejorative ways because of their addiction. All participants reported experienced or anticipated stigma related to drug use. Our participants described avoiding seeking medical care and developing strategies to deal with anticipated and experienced stigma; some reported their minimization of physical complaints due to providers’ focus on their substance use as well as medical care being withheld because of their substance use. Three themes emerged around experiences of care that conferred dignity and autonomy: 1) experience dignity in and through use and access of harm reduction services, 2) peer support as a tool to model for relational harm reduction 3) harm reduction as community care (leveraging a responsibility to look out for others). Participants identified these social supports as giving them hope and motivation around their own health goals. Conclusion Our findings emphasize that healthcare settings remain challenging for PWUD. Patients describe how stigmatizing beliefs impact clinical reasoning and bleed into negative healthcare experiences and lower quality of care. The foundational principles of harm reduction – appreciating the social contexts in which individuals use drugs and the dignity in survival strategies – offer pathways for therapeutic communication between patients and providers.